PRDM16 Enhances Osteoblastogenic RUNX2 via Canonical WNT10b/β-CATENIN Pathway in Testosterone-Treated Hypogonadal Men - Siresha Bathina; Mia Prado; Virginia Fuenmayor Lopez; Georgia Colleluori; Lina Aguirre; Rui Chen; Dennis T. Villareal; Reina Armamento-Villareal (Biomolecules)
We previously reported that PRDM16 mediated the improvement in body composition in testosterone (T)-treated hypogonadal men by shifting adipogenesis to myogenesis. Previous preclinical studies suggest that Prdm16 regulates Runx2, an important osteoblastic transcription factor, expression and activity. However, the changes in PRDM16, and other genes/proteins involved in osteoblastogenesis with T therapy in hypogonadal men are unexplored. We investigated the role of PRDM16 in RUNX2 activation by measuring changes in gene expression in peripheral blood monocytes (PBMCs) and proteins in the serum of hypogonadal men after T therapy for 6 months. Likewise, we evaluated changes in the WNT10b—β-CATENIN signaling pathway by gene expression and protein analyses. We found significant increases in PRDM16 and RUNX2 expression in PBMCs together with significant increases in serum proteins at 6 months when compared to baseline. There were also increases in gene and protein expressions of WNT10b, and β-CATENIN at 6 months. Furthermore, we found a significant positive correlation between % changes in PRDM16 and WNT10b. Our results suggest that T therapy activates PRDM16, leading to enhanced signaling in the canonical WNT10b—β-CATENIN-RUNX2 pathway, the pathway involved in osteoblastogenesis. The above findings may account for the improvement in bone density and quality in hypogonadal men treated with T.